Combination chemotherapy with paclitaxel, cisplatin and fluorouracil for patients with advanced and metastatic gastric or esophagogastric junction adenocarcinoma: a multicenter prospective study - Zhang, Xiaodong; Shu, Yongqian; Liang, Jun; Zhang, Fengchun; Ma, Xuezhen; Huang, Jianjin; Chen, Li; Shi, Genming; Cao, Weiguo; Guo, Chengye; Shen, Lin; Jin, Maolin (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Gastric cancer (AGC) and esophagogastric junction (GEJ) adenocarcinoma remains one of the most common causes of cancer death worldwide, especially in Asia. Advanced gastric cancer patients have a poor prognosis (1-4). Incidence of gastric cancer in China is very high, and more than half of chinese patients are in advanced stage at first diagnosis, with unresectable locally advanced, or metastatic disease. Median survival of advanced gastric cancer is only 6-10 months. How to control the disease, and improve the outcome of patients with local advanced metastatic disease is still a major challenge (5,6). Taxanes (paclitaxel and docetaxel) have been studied in AGC as a single agent or combination (7-11). A large randomized phase III study (V325) showed increased efficacy with the combination of DCF (docitaxel, cisplatin and 5-FU), however, the toxicity profile of regimen (up to 82% of grade 3/4 hematological toxicity) made it hard to apply in clinic practice (11). It has also been also noticed that Chinese patients tolerate to chemotherapy less well than Western populations (12,13). Domestic prospective multi-center studies are needed for Chinese advanced AGC patients.